Young Women's Reproductive Health (Ethnographic Study Oon Young Women's Knowledge and Behavior Related to Reproductive Health In Bantan Village Slums Medan Tembung) - Siahaan, Febri; Fitria Harahap, Aida (Indonesian Journal of Medical Anthropology, 2020)
This study discusses how the knowledge and behavior of young women in slums are related to reproductive health. The purpose of this study is to describe the knowledge and behavior of young women in slums. Whether the influence of slum environments with adolescent social behavior, how parents play in providing reproductive health education to their daughters, and how the rules exist in society limit young women's sexual behavior. The research method used in i research is a qualitative approach. The data collection techniques used are interviews and observations to the public. The result of the study is that reproductive health is understood as a matter of how to maintain the cleanliness of reproductive organs to avoid disease. The scope of the conversation also concerns sexual intercourse conducted by men and women. Parents usually provide knowledge of this only in the form of straightforward advice. Meanwhile, the local community also imposes moral sanctions in the form of censure, innuendo for deviant young women.